Determinants of Junk Food Consumption Among Adolescents in Pokhara Valley, Nepal - Bohara, Suraj Sujan; Thapa, Kanchan; Bhatt, Laxman Datt; Dhami, Shankar Singh; Wagle, Shreejana (Frontiers in Nutrition, 2021)
Background: Junk food consumption and its consequences has become a major public health concern globally because of its deteriorating health consequences and surging prevalence. Though its adverse health consequences are widely prevalent in all age groups, children and adolescents are more at risk. It may lead to obesity and act as a risk factor for different non-communicable diseases (NCD’s) like heart diseases, cardiovascular disease, cancer, hypertension, diabetes etc. This study was carried out to explore the junk food consumption and its associated factors among adolescent students. Methods: A cross-sectional study was conducted among 538 adolescent students of Kaski district, Nepal. We used a stratified proportionate sampling technique to recruit the participants. A self-administered questionnaire was used for data collection. Descriptive and bivariate statistical analysis were performed. The odds ratio was computed to test the association. Results: The study found that more than half of the participants (60.30 %) consumed junk food over the last 30 days, more prevalent among public school participants (65.1%) followed by participants of private school (56.3%). More than one-quarter of the participants consumed salty snacks (58.7 %) followed by sweets (57.5%). Time of consumption was found to be higher together with friends (83.9 %). Similarly, it was consumed more while participants were during the trip (70.1 %). Consumption of junk food was significantly associated with public school(OR:1.44,CI=1.01-2.06), single-family (OR:1.46, CI=1.01-2.10), living with parents (OR:1.64, CI=1.03-2.63), while on travel (OR:1.99, CI=1.33-2.98), while on reading (OR:2.01, CI=1.16-3.47), at home (OR:2.20, CI=1.53-3.16), at school (OR:2.86, CI=1.98-4.12), friends influence (OR:2.01, CI=1.37-2.94) and junk food availability at home (OR:1.92, CI=1.33-2.76). Conclusion: Consumption of junk food among adolescent students was remarkably high in both public school and private school adolescents. Regardless of adequate knowledge on harmful consequences of junk foods, school going adolescents are consuming junk food due to its easy availability, ready to use packaging. Government of Nepal should strictly standardize and regulate advertising policies and extravagant health claims advertise by junk food manufacturer. An appropriate intervention targeted to adolescents to improve food behaviors is recommended.